Discovery of ginisortamab, a potent and novel anti-gremlin-1 antibody in clinical development for the treatment of cancer - Gareth C. G. Davies; Neesha Dedi; Paul S. Jones; Lara Kevorkian; David McMillan; Cristina Ottone; Monika-Sarah E. D. Schulze; Anthony Scott-Tucker; Roohi Tewari; Shauna West; Michael Wright; Tania F. Rowley (mAbs)
Gremlin-1, a high-affinity antagonist of bone morphogenetic proteins (BMP)-2, −4, and −7, is implicated in tumor initiation and progression. Increased gremlin-1 expression, and therefore suppressed BMP signaling, correlates with poor prognosis in a range of cancer types. A lack of published work using therapeutic modalities has precluded the testing of the hypothesis that blocking the gremlin-1/BMP interaction will provide benefits to patients. To address this shortfall, we developed ginisortamab (UCB6114), a first-in-class clinical anti-human gremlin-1 antibody, currently in clinical development for the treatment of cancer, along with its murine analog antibody Ab7326 mouse immunoglobulin G1 (mIgG1). Surface plasmon resonance assays revealed that ginisortamab and Ab7326 mIgG1 had similar affinities for human and mouse gremlin-1, with mean equilibrium dissociation constants of 87 pM and 61 pM, respectively. The gremlin-1/Ab7326 antigen-binding fragment (Fab) crystal structure revealed a gremlin-1 dimer with a Fab molecule bound to each monomer that blocked BMP binding. In cell culture experiments, ginisortamab fully blocked the activity of recombinant human gremlin-1, and restored BMP signaling pathways in human colorectal cancer (CRC) cell lines. Furthermore, in a human CRC – fibroblast co-culture system where gremlin-1 is produced by the fibroblasts, ginisortamab restored BMP signaling in both the CRC cells and fibroblasts, demonstrating its activity in a relevant human tumor microenvironment model. The safety and efficacy of ginisortamab are currently being evaluated in a Phase 1/2 clinical trial in patients with advanced solid tumors (NCT04393298).